Does Internal Control Promote Employee Engagement Drivers? A Systematic Literature Review - Haryanto Haryanto; Harry Suharman; Poppy S. Koeswayo; Haryono Umar (Australasian Accounting, Business and Finance Journal, 2023)
Internal control (IC) and employee engagement (EE) are critical organizational factors, whereby one is part of accounting principles, while the other is under the human resource domain. This study investigates the linkage between the implementation of IC and the factors that drive EE, specifically, how internal control measures impact employee engagement drivers. The research uses a systematic literature review by reviewing published articles about EE in journals published by Web of Science, Scopus, and Google Scholar from 2013–2022. The results show that internal control practices can also resonate as the drivers of EE. The findings mean that an organization will benefit from implementing internal control correctly because it will serve two objectives. The first objective is to ensure record accuracy, boost operational efficiency, reduce risks, safeguard assets, and encourage compliance with laws, policies, and regulations. The second objective is to promote employee engagement levels. The findings offer opportunities for further empirical research to back up the conclusions drawn here and better comprehend the business world's reality.
Keywords: Internal Control; Employee Engagement Drivers; Systematic Literature Review.